Sustainable Pavement Design: Synergistic Effects of Buton Rock Asphalt and Recycled PET on Asphalt Performance - Nawir, Daud; Mansur, Achmad Z. (Civil Engineering Journal, 2026)
This study presents a comprehensive investigation into the synergistic effects of Buton Rock Asphalt (BRA) and Powdered Bottle Flakes (PBF) as sustainable modifiers for asphalt concrete mixtures. Employing a rigorous factorial experimental design, we tested 12 distinct combinations of BRA and PBF, with the Optimum Asphalt Content (OAC) consistently determined to be 5.5%. Results from Marshall testing demonstrated that incorporating these two materials significantly enhanced the mixture's stability and stiffness. These findings were further corroborated by advanced durability tests, which confirmed exceptional performance, with a Retained Stability Index (RSI) exceeding 80% and minimal mass loss in the Cantabro test. The improved performance is attributed to the strong synergy between the hard bitumen from BRA and the polymeric matrix formed by PBF. This combination not only effectively reduced Voids in the Mix (VIM), resulting in a denser structure, but also exhibited superior resistance to permanent deformation. However, our analysis identified a critical trade-off: using the highest proportions of these modifiers may produce overly stiff mixtures, potentially increasing the risk of cracking. Overall, this research confirms that the BRA-PBF combination is a highly effective and sustainable solution for enhancing the mechanical performance and durability of road pavements. It provides a robust scientific foundation for developing a balanced mixture design that achieves optimal long-term performance.